Representasi Kesehatan Mental dan Pesan Moral dalam Komik “Beban di Balik Senyuman”: Kajian Semiotika - Mardiyah, Azimah; Azkiya, Haura; Salsabila, Naurah (P3M Politeknik Negeri Media Kreatif, 2025)
The development of technology makes literary works have various forms, one of which is in the form of digital comics that can be accessed anywhere easily. This study analyzes a digital comic entitled